PECULIARITIES OF PREPARATION OF FUTURE SOFTWARE ENGINEER FOR PEDAGOGICAL ACTIVITY - Sedov В.Є. (Journal of Information Technologies in Education (ITE), 2015)
The article shows the main results of the study of the current state of the system of masters training in information technology in higher education institutions, including the analysis of interim educational and vocational programs of specialist and master of training direction "Software Engineering" (branch of knowledge 0501 "Informatics and Computer Science") and the "Informatics" ("System Sciences and Cybernetics") and curricula of appropriate specialties in terms of the presence the disciplines most suitable for the formation of psycho-pedagogical competence of future engineers programmers. In particular the dynamics of methods, forms and technologies of education are examined; the certain areas of teaching IT professionals at universities and IT companies are highlighted. The attention is brought to the existence of certain contradictions in the system for masters training in information technologies and the need to attract highly qualified specialists- practitioners in condutcing the classes in Master System, the need for flexibility in the learning process.